An experimental study of acute subarachnoid haemorrhage in baboons: changes in cerebral blood volume, blood flow, electrical activity and water content. Issue 4 (April 1984) - Kuyama, H; Ladds, A; Branston, N M; Nitta, M; Symon, L
Abstract : Subarachnoid haemorrhage following transection of the posterior artery was produced in 10 baboons. Cerebral blood volume (CBV) decreased transiently after subarachnoid haemorrhage. Two basic patterns of intracranial pressure (ICP) were observed; in one ICP returned to normal but in the other it remained elevated. In this latter group four out of five animals showed an increase in CBV above the original level. There were delays in sensory conduction (measured using somatosensory evoked potentials) bilaterally; those on the contralateral side to the bleed were correlated with ICP whereas other factors are implicated on the ipsilateral side. Initial flow reduction and restoration of cerebral blood flow were both correlated with water content.